Flood Monitoring System using Internet of Things (IoT) - Abdullah, Mohamad Alif Aiman; Abdul Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2024)
There have been severe floods in certain parts of Malaysia recently. It strikes quickly and has an impact on many different types of individuals and structures. Most individuals are unable to forecast when the next flood will occur because they do not have access to trustworthy information on weather trends. The development and design of an Internet of Things (IoT) flood monitoring system with the capability to identify possible flooding situations is the primary goal of this project. In order to simulate flood submergence, this project uses an pp float switch water level sensor to measure the height of the floodwater in a laboratory-scale terrain modality. In this setup, a Durian UNO serves as the microcontroller, and data is sent from the microcontroller to the Blynk application via the WIFI module (ESP 8266). Additionally, this system has a buzzer that will sound when the floodwater level rises when achieve ‘HIGH’ level. When the water level reach danger level or ‘HIGH’ was reached, the system would notify the user via the Blynk app and the Blynk dashboard colour will turn yellow if in ‘MEDIUM’ condition and will turn red if in ‘HIGH’ condition. By informing users when a flood is imminent, this Internet of Things flood monitoring device could help save lives and property in flood-prone areas.